MENINGKATKAN PERILAKU SOSIAL ANAK MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD KELOMPOK B3 DI TK PEMBINA NEGERI 1 BANGKO KABUPATEN ROKAN HILIR - Fitriani, Mira; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Improving Children's Social Behaviour Through Application of Cooperative Learning STAD type B3 Group in kindergarten Pembina State 1 Bangko Rokan Hilir Academic Year 2014/2015. Thesis 2015. The background of this study is the lack of learning, children like to mock his friend who has a low background, children like to talk with his rough when playing, the child does not want to share toys or food to her son liked to mock other people's work. Therefore, it is necessary efforts to improve the social behavior of children, namely the implementation of STAD cooperative learning. The purpose of this study was to determine whether there is an increase in the ability of social behavior of children through the implementation of STAD cooperative learning and to find out how the increase that occurred. This research is a classroom action research conducted in two cycles. Data collection tool used in this study is in the form of observation sheet. The number of samples in this study were 17 children consisting of 8 boys and 9 girls.Based on the analysis of the assessment process there was an increase of 2 cycles. Improvement occurred, ie from before the action kesiklus I is 33.02%, the first cycle kesiklus II amounted to 38.27% and the increase of the prior cycle kesiklus II of 81.38%. From the results mentioned penilitian can be concluded that through the implementation of STAD cooperative learning can improve social behavior of children aged 5-6 years in kindergarten Pembina State 1 Bangko Rokan Hilir.Keywors : Prilaku sosial, kooperatif tipe STAD